Whole-body CT scanning radiation improves the immune microenvironment of tumor tissues to enhance the antitumor effect of ICI - Jigang Dong; Ying Qi; Sha Sha; Chengrui Fu; Xiao Xu; Baosheng Li (BMC Cancer)
Abstract Objective The effect of frequent whole-body CT scans during immune checkpoint inhibitor (ICI) therapy on patients' anti-tumor immunity. Methods We conducted a retrospective clinical study aimed to investigate the correlation between the frequency of CT scans during immune checkpoint inhibitor (ICI) therapy and the duration of remission (DOR) of ICI therapy in patients with stage IV non-small cell lung cancer (NSCLC). We constructed a hormonal mouse model and administered immune checkpoint inhibitor (ICI) therapy to mice, and radiated five whole-body CT scans to mice during ICI therapy to observe whether frequent whole-body CT scans had an effect on the antitumor effect of immunotherapy in mice. Results The more frequent CT scans during patients' immune checkpoint inhibitor (ICI) treatment the longer the duration of remission (DOR) of ICI treatment. In a mouse model we observed that the addition of whole-body CT scanning radiation had a tendency to inhibit tumor growth in mice compared with the anti-PD-1 group alone.Frequent CT scanning radiation during the application of immune checkpoint inhibitor PD-1 increased the proportion of infiltrating CD8 + T cells in tumor tissues and significantly increased the proportion of IFNγ-secreting CD8 + T cells, and single-cell sequencing of the results also revealed that IFNγ and killing-related genes were significantly upregulated in tumor-infiltrating CD8T cells. Conclusion To our knowledge this is the first study on the effect of CT scan radiation on ICI.Our findings suggest that multiple CT scans during immune checkpoint inhibitor (ICI) treatment did not promote tumor progression, but instead a trend toward delayed tumor progression was observed.